Meningoencephalitis in a Young Immunocompetent Patient - Michael Ke MD; Neeki Ettefagh; Ahmet Semih Topbas MD; Mehdi Kazemi MD (Journal of Investigative Medicine High Impact Case Reports)
Cryptococcal meningitis is mainly seen in immunocompromised patients, but in recent years, there has been an increase in cases involving patients with no known immunodeficiencies. These patients have symptomatic presentations that range from indolent and mild to typical and severe. We present a case of cryptococcal meningitis in an immunocompetent young patient with a chronic headache. The patient underwent imaging which showed diffuse leptomeningeal enhancement and a lumbar puncture which confirmed Cryptococcus neoformans . She underwent guideline-based treatment for cryptococcal meningitis and improved clinically. Cryptococcal meningitis should be considered in immunocompetent patients who present with typical signs of symptoms of meningitis, particularly chronic headaches and altered mental status.